2015
DOI: 10.1161/circulationaha.115.017119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Heart Rate Slowing in Heart Failure With Preserved Ejection Fraction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 44 publications
2
79
2
2
Order By: Relevance
“…18 In our study, the use of ivabradine was associated with a reduction in heart rate and significant improvement of modified Borg scale and 6-minute walk distance. In another study, Pal et al 19 found that heart rate reduction with ivabradine was not associated with an improvement in exercise capacity. That study included different categories of patients; namely heart failure with preserved ejection fraction (HFpEF) and asymptomatic hypertensives.…”
Section: Discussionmentioning
confidence: 94%
“…18 In our study, the use of ivabradine was associated with a reduction in heart rate and significant improvement of modified Borg scale and 6-minute walk distance. In another study, Pal et al 19 found that heart rate reduction with ivabradine was not associated with an improvement in exercise capacity. That study included different categories of patients; namely heart failure with preserved ejection fraction (HFpEF) and asymptomatic hypertensives.…”
Section: Discussionmentioning
confidence: 94%
“…61 The second study administered ivabradine 7.5 mg twice daily in a crossover design to 22 patients with HFpEF. 62 Although ivabradine improved echocardiographic parameters of diastolic function over 2 weeks, it diminished peak oxygen consumption and submaximal exercise performance measured by oxygen uptake efficiency slope.…”
Section: Hf With Preserved Ejection Fractionmentioning
confidence: 96%
“…HR decreased ≈10 bpm in the low-dose trial compared with 20 bpm in the higher-dose trial. 61,62 Given the heterogeneity of HFpEF diagnoses, additional uncharacterized differences in the subjects were likely. 63 More evidence is needed to determine the potential role for ivabradine in patients with HFpEF.…”
Section: Hf With Preserved Ejection Fractionmentioning
confidence: 99%
“…Because many HFpEF patients only show HF symptoms during exercise, ivabradine treatment may be beneficial in HFpEF patients. However, a randomized crossover study [84] examined the effect of ivabradine treatment on exercise capacity in 22 symptomatic HFpEF patients with objective evidence of exercise limitation compared to placebo. Study results were compared with 22 similarly treated matched asymptomatic hypertensive volunteers.…”
Section: Ivabradinementioning
confidence: 99%